Pengaruh Penambahan Puree Buah Nangka (Artocarpus heterophyllus) Terhadap Karakteristik Marshmallows - Putu Kartika Dewi, Dewa Ayu; Ayu Ekawati, I Gusti; Sri Wiadnyani, Anak agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i02.p09, 2022)
Marshmallows are fluffy, foamy candies that come in a variety of shapes, aromas, flavors, and colors. The aim of this study is to determine the impact of adding jackfruit puree on marshmallows characteristics, as well as the amount of jackfruit puree that produces the best marshmallows. The Complete Randomized Design (CRD) was used in this analysis, and it included 5 levels of jackfruit puree addition: 0%, 20%, 40%, 60%, and 80%. To acquire 15 experimental units, each procedure was repeated 3 times. The data was analyzed using analysis of variance, and the Duncan Multiple Range Test (DMRT) was used if the procedure had a major impact. Water content, ash content, reduced sugar content, aroma, texture, taste, overall acceptance (hedonic test), aroma and taste (skoring test). The addition of 60% jackfruit puree produces marshmallows with the best characteristics, namely water content of 33.07%, ash content of 0.20%, reduced sugar content of 64.64%, color liked, aroma liked and strong jackfruit aroma, texture liked and slightly chewy, taste liked and taste strong jackfruit, and overall acceptance liked.